Pola Komunikasi Mahasiswa Kristen dalam Beradaptasi dengan Mahasiswa Islam di Fakultas Ilmu Sosial Universitas Islam Negeri Sumatera Utara - Fitri Holila Siregar; Zuhriah Zuhriah (Jurnal Multidisiplin Indonesia, 2026)
This study aims to analyze the communication patterns of Christian students in adapting to Muslim students at the Faculty of Social Sciences, State Islamic University of North Sumatra (UINSU). The study focuses on communication strategies, adaptation processes, communication barriers, and the role of intercultural communication in fostering social relationships within a multicultural campus environment. This research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews with four Christian students enrolled at the Faculty of Social Sciences, UINSU. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that two-way communication serves as the primary strategy used by Christian students in adapting to Muslim students. Open communication, mutual respect, and positive feedback contribute significantly to the development of harmonious social relationships. Furthermore, intercultural communication plays an essential role in enhancing interreligious understanding, reducing stereotypes, and strengthening tolerance within the campus community. The communication barriers identified were relatively minor, primarily involving difficulties in understanding Arabic terms frequently used in daily conversations. Meanwhile, adaptation challenges were mainly related to adjustments to campus culture and regulations, particularly regarding dress codes. The findings indicate that the successful adaptation of Christian students in an Islamic campus environment is supported by effective interpersonal communication, tolerance, and an inclusive academic atmosphere. This study confirms that two-way communication and intercultural communication are crucial factors in promoting social integration and creating harmonious campus life amid religious diversity.